On composing Dependable Web Services using undependable web components. (27th July 2007) - Gorbenko, Anatoliy; Kharchenko, Vyacheslav; Romanovsky, Alexander
This paper proposes a novel approach to constructing and modelling Dependable Web Services (DeW) that are built by composing web components that can be undependable. This is achieved by applying a structured approach to the Web Services (WSs) development, based on the Web Service Composition Actions (WSCAs) scheme and a corresponding event-driven simulation model of composite WS. The dependability and fault-tolerance of composite WS is achieved by employing forward error recovery based on multilevel system structuring enabling application-specific exception handling.